Literacy learning problems: Developing the character of reading fondness in elementary school students during the covid-19 - Rahmat Aziz; Djoko Susanto; Sabilla Irwina Safitri; Lina Izza Mazida; Thomas Wijaya (Universitas PGRI Madiun, 2021)
Learning activities in developing the character of reading fondness in elementary school students during the COVID-19 period have raised various difficulties for both teachers as directors of the learning process and students as learning implementers. Challenges that are not responded to appropriately and wisely by schools have resulted in low reading habits. This paper aims to describe student reading behaviour and analyze the teacher's role during the learning process. Data were obtained through an online questionnaire from 122 students and seven teachers in three elementary schools in Riau, Central Kalimantan, and East Java. The data were analyzed using thematic analysis and reflective thinking. The results show that responsive and proportional teachers in delivering learning have succeeded in developing reading behaviour in students. This paper suggests the need for more in-depth data collection methods to understand the case better.